Phage Therapy as a Novel Strategy in the Treatment of Urinary Tract Infections Caused by E. Coli - Beata Zalewska-Piątek; Rafał Piątek (MDPI AG, 2020)
Urinary tract infections (UTIs) are regarded as one of the most common bacterial infections affecting millions of people, in all age groups, annually in the world. The major causative agent of complicated and uncomplicated UTIs are uropathogenic E. coli strains (UPECs). Huge problems with infections of this type are their chronicity and periodic recurrences. Other disadvantages that are associated with UTIs are accompanying complications and high costs of health care, systematically increasing resistance of uropathogens to routinely used antibiotics, as well as biofilm formation by them. This creates the need to develop new approaches for the prevention and treatment of UTIs, among which phage therapy has a dominant potential to eliminate uropathogens within urinary tract. Due to the growing interest in such therapy in the last decade, the bacteriophages (natural, genetically modified, engineered, or combined with antibiotics or disinfectants) represent an innovative antimicrobial alternative and a strategy for managing the resistance of uropathogenic microorganisms and controlling UTIs.